Brassinosteroid-regulated GSK3/Shaggy-like Kinases Phosphorylate Mitogen-activated Protein (MAP) Kinase Kinases, Which Control Stomata Development in Arabidopsis thaliana - Khan, Mamoona (American Society for Biochemistry and Molecular Biology, 2013)
Brassinosteroids (BRs) are steroid hormones that coordinate fundamental developmental programs in plants. In this study we show that in addition to the well established roles of BRs in regulating cell elongation and cell division events, BRs also govern cell fate decisions during stomata development in Arabidopsis thaliana. In wild-type A. thaliana, stomatal distribution follows the one-cell spacing rule; that is, adjacent stomata are spaced by at least one intervening pavement cell. This rule is interrupted in BR-deficient and BR signaling-deficient A. thaliana mutants, resulting in clustered stomata. We demonstrate that BIN2 and its homologues, GSK3/Shaggy-like kinases involved in BR signaling, can phosphorylate the MAPK kinases MKK4 and MKK5, which are members of the MAPK module YODA-MKK4/5-MPK3/6 that controls stomata development and patterning. BIN2 phosphorylates a GSK3/Shaggy-like kinase recognition motif in MKK4, which reduces MKK4 activity against its substrate MPK6 in vitro. In vivo we show that MKK4 and MKK5 act downstream of BR signaling because their overexpression rescued stomata patterning defects in BR-deficient plants. A model is proposed in which GSK3-mediated phosphorylation of MKK4 and MKK5 enables for a dynamic integration of endogenous or environmental cues signaled by BRs into cell fate decisions governed by the YODA-MKK4/5-MPK3/6 module.